ANALYSIS OF COMMUNICATION PATTERNS AND INTERCULTURAL CONFLICT IN OVERCOMING LANGUAGE BARRIERS BETWEEN FOREIGN COACHES AND ATHLETES AT YASANIS WUSHU TRAINING CENTER, SURABAYA - Achmad An’im Zaidan Abu Zaki; Roziana Febrianita (Adisam Publisher, 2026)
This study aims to analyze intercultural communication patterns, forms of communication conflict, and strategies for overcoming language barriers between foreign coaches and athletes at Yasanis Wushu Training Center, Surabaya. The study employed a descriptive qualitative approach, with data collected through passive participant observation, semi-structured in-depth interviews, and documentation. The research participants consisted of one coach from China and four wushu athletes selected using a purposive sampling technique. Data were analyzed using the Miles and Huberman interactive model, which involves the stages of data reduction, data display, and conclusion drawing. The findings reveal that communication between the coach and the athletes was predominantly characterized by a high-context communication pattern, relying primarily on movement demonstrations, nonverbal expressions, and direct corrective feedback as the principal means of delivering instructions. Language barriers emerged as the primary challenge, giving rise to misunderstandings, uncertainty, and communication conflicts resulting from differences in language, culture, and communication styles. Nevertheless, these conflicts did not escalate into destructive conflicts, as both parties were able to adapt through repeated instructions, movement demonstrations, the use of nonverbal communication, assistance from interpreters in specific situations, and mutual efforts to learn each other's language. The sustained intensity of interaction also fostered mutual understanding, reduced anxiety and uncertainty, and enhanced communication effectiveness. The findings underscore that the ability to adapt to linguistic and cultural differences is a crucial factor in establishing effective communication while supporting the successful development of athletes within a multicultural high-performance sports environment.